Simplification of separation of reaction mixture after transesterification of vegetable oil - Hájek, Martin; Skopal, František; Machek, Jaroslav (Wiley-Blackwell, 2008)
Heterogeneous reaction mixture is formed by transesterification of vegetable oils. The reaction mixture contains methyl esters of higher fatty acids and glycerol mainly. From this mixture, biodiesel is gained by spontaneous sedimentation in the gravitational field. The sedimentation can be considerably accelerated by controlled addition of water. It was found that addition of small amount of water into the crude reaction mixture affected significantly the mixture and substantial change in the speed of the separation took place. Considerable differences in the composition and quality of ester and glycerol phases occurred. Optical properties (transmittance and refractive indices) of heterogeneous reaction mixture are change after addition of water; this change can be observed spectrophotometrically. This method is applicable for all types of vegetable oils including waste frying oils.
Keywords: Biodiesel; vegetable oil; sedimentation; Water; refractive index